Health Communication Practice among Rural Communities In Sabah, Malaysia: Issues of Literacy, Accessibility and Availability and Communication Approach - Abdul Karim, Haryati (Journal of Contemporary Issues in Media & Communication (JCIMC), 2023)
This paper seeks to highlight the need to improve the communication approaches taken by the Ministry of Health, Malaysia, to uplift the health literacy rate among rural communities. The World Health Organization (WHO) defines health literacy as the cognitive and social ability of people to gain access to health information so as to make informed decisions concerning their health. However, a study on health literacy conducted in four districts in Sabah, namely Nabawan, Ranau, Beaufort and Kota Belud, found that several factors hampered the access of the rural communities to health information, hence, contributing to their lack of awareness about health and healthcare. Based on in-depth interviews with 42 informants from the four districts, the study found that the rural communities faced various factors, such as poverty, media literacy and limited media access, which prevented them from obtaining health information and achieve health literacy. Their only source of health information was through consultations with doctors whenever they or their family members were sick. The informants said that they found public health talks to be most helpful for them to learn about diseases because these were interactive, and also aided those who were illiterate and had no television sets in their homes. They expressed the hope that more talks would be given regularly about chronic diseases, which many of them were already suffering from. This study suggests that Health Departments intensify their outreach through health education programmes based on interpersonal communication, rather than through the use of social media, to increase the health literacy rate among rural communities.